Divergent epidermal growth factor receptor mutation patterns between smokers and non-smokers with lung adenocarcinoma. Issue 3 (December 2015) - Tseng, Jeng-Sen; Wang, Chih-Liang; Yang, Tsung-Ying; Chen, Chih-Yi; Yang, Cheng-Ta; Chen, Kun-Chieh; Hsu, Kuo-Hsuan; Tsai, Chi-Ren; Chang, Gee-Chen
Highlights: A multicenter cohort that consisted of 1175 lung adenocarcinoma patients were conducted for EGFR mutation analysis. Smoking status not only influenced the frequency but also the patterns of EGFR mutations. Subtypes of 19Del and L858R were also different between smokers and non-smokers. Abstract: Introduction: Smoking status is an important determinant of the prevalence of epidermal growth factor receptor ( EGFR ) mutations in lung cancer patients. However, it is unclear whether smoking status could also influence the spectrum of EGFR mutations. Methods: We enrolled patients with lung adenocarcinoma from three medical centers in Taiwan. EGFR mutations were assessed by Sanger direct sequencing. The objective of this study was to evaluate the influence of smoking status on both the frequency and patterns of EGFR mutations. Results: From 2001 to 2013, a total of 1175 patients with lung adenocarcinoma were enrolled for EGFR mutation analysis. The overall EGFR mutation rate was 59.6%, which was significantly higher in females than males (69.1% vs. 49.8%) and in non-smokers than current/former smokers (73.8% vs. 29.8%) (both P  < 0.001). Among patients harboring EGFR mutations, smokers expressed L858R mutation less frequently (35.2% vs. 50.2%, P  = 0.005) and exon 19 deletions more frequently (52.8% vs 38.8%, P  = 0.008) than non-smokers. Smokers and non-smokers also had divergent exon 19 deletions subtypes (Del E746-A750 82.5% vs. 57.6%, respectively, P  < 0.001). Among subgroup patients harboring the L858R mutation, smokers were associated with a higher rate of complex mutations than non-smokers (34.2% vs. 8.4%, P  < 0.001). Conclusions: Our results suggested that smoking status could influence not only the frequency but also the spectrum of EGFR mutations. These findings provide a clue for further investigation of EGFR mutagenesis.